La christologie d’Ephésiens - Hermans, Robert (Biblica, 2011)
This essay proposes to read Eph 1,23, as follows: the plh/rwma is Christ, the fullness of all God’s graces. And the participle plhroume/nou is a neuter passive, whose content is the actual blessing brought by God to its fullness in all the believers. Eph 1,23 can then be translated like this: «Christ is the fullness of what is fully accomplished in all the faithful».